2009
DOI: 10.1016/j.ijsolstr.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic equivalence, self-equilibrated excitation and Saint-Venant’s principle for an elastic strip

Abstract: a b s t r a c tThe distinction between the near and far-fields for a semi-infinite, elastic strip has been exploited to derive conditions under which different dynamic excitations can be considered as equivalent. These different excitations are equivalent in the sense that they produce the same displacement field far from the excited end. It is shown that dynamically equivalent excitations degenerate to statically equivalent loads in the limit of a vanishing frequency. The no-radiation condition is derived, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 35 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…These loads are termed dynamically equivalent, and as such, illustrate the interpretation and the validity of DSVP suggested by Karp (2009). According to that interpretation, two dynamically equivalent loads will generate identical strain filed far from the loaded area.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…These loads are termed dynamically equivalent, and as such, illustrate the interpretation and the validity of DSVP suggested by Karp (2009). According to that interpretation, two dynamically equivalent loads will generate identical strain filed far from the loaded area.…”
Section: Discussionmentioning
confidence: 92%
“…That interpretation is not a simple extension of the classical SVP since in the static case the equivalence is judged upon static equivalents, while here, the equivalence is judged upon average power (intensity) of the excitation. Nevertheless, it was shown that both interpretations coincide in the limit of vanishing frequency (Karp, 2009). Since the dynamic response of the whole strip can not be identical for differently distributed loads, let us seek the differences in response of the strip subjected to any dynamically equivalent loads.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations